Growth Performance and Brood Stock Management of Small Indigenous Fish Mola Carplet, Amblypharyngodon mola (Hamilton, 1822) - Nayak, S.; Panda, B.; Radhakrishnan, K.; Verma, D.K.; Das, K.C.; Routray, P. (Indian Journal of Animal Nutrition, 2021)
Spontaneous spawning of wild caught and domesticated mola carplet, Amblypharyngodon mola was attempted in controlled condition using an aquatic plant hydrilla, Hydrilla verticillata as a modified habitat. Growth performance of hatched larvae revealed that the larval growth (weight gain %) was significantly higher (p 80 %) of mola was observed in tanks/ ponds having hydrilla as an additional habitat than the tanks /ponds having no hydrilla.  Similarly, higher fecundity of mola (>900) was recorded in tanks having hydrilla. Better spawning performance was also noted using hydrilla based habitat. The findings can be useful in artificial propagation and diversification of small indigenous fish species in captivity.